Design of an Efficient Face Recognition Algorithm based on Hybrid Method of Eigen Faces and Gabor Filter - Abdulmunem, Matheel E.; Ibrahim, Fatima B. (Iraqi Journal of Science, 2022)
Face recognition is one of the most applications interesting in computer vision and pattern recognition fields. This is for many reasons; the most important of them are the availability and easy access by sensors. Face recognition system can be a sub-system of many applications. In this paper, an efficient face recognition algorithm is proposed based on the accuracy of Gabor filter for feature extraction and computing the Eigen faces. In this work, efficient compressed feature vector approach is proposed. This compression for feature vector gives a good recognition rate reaches to 100% and reduced the complexity of computing Eigen faces. Faces94 data base was used to test method.